Application of cavitation system to accelerate aqueous enzymatic extraction of seed oil from Cucurbita pepo L. and evaluation of hypoglycemic effect. (1st December 2016) - Li, Xiao-Juan; Li, Zhu-Gang; Wang, Xun; Han, Jun-Yan; Zhang, Bo; Fu, Yu-Jie; Zhao, Chun-Jian
Graphical abstract: Highlights: Cavitation-accelerated aqueous enzymatic extraction is green and effective. CAEE-oil exhibited better oxidation stability than Soxhlet derived-oil. Cucurbita pepo L. oil is proven to be a potential anti-diabetic agent in human diets. Abstract: Cavitation-accelerated aqueous enzymatic extraction (CAEE) of seed oil from Cucurbita pepo was performed. An enzyme cocktail comprised of cellulose, pectinase and proteinase can work synergistically in releasing the oil. The CAEE extraction conditions were optimized by a Plackett-Burman design followed by a central composite methodology. A maximal extraction yield of 58.06% was achieved under optimal conditions of vacuum degree −0.07, enzyme amount 1.05% and extraction time 69 min. As compared to soxhlet extraction (SE)-derived oil, CAEE-derived oil exhibited similar physical properties and better oxidation stability. In addition, chemical composition analyzing showed that the content of linoleic acid obtained by CAEE (47.67%) was higher than that of SE (44.51%). Moreover, the IC50 of oil obtained by CAEE and SE, as measured by α-amylase inhibition assay, were 40.68 μg/mL and 45.46 μg/mL. All results suggest that CAEE represents an excellent alternative protocol for production of oil from oil-bearing materials.